2011
DOI: 10.1007/s10570-011-9541-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wet-pressing-induced fiber hornification on enzymatic saccharification of lignocelluloses

Abstract: This article reports the effect of wetpressing-induced fiber hornification on enzymatic saccharification of lignocelluloses. A wet cellulosic substrate of bleached kraft eucalyptus pulp and two wet sulfite-pretreated lignocellulosic substrates of aspen and lodgepole pine were pressed to various moisture (solids) contents by variation of pressing pressure and pressing duration. Wet pressing reduced substrate moisture content and produced irreversible reduction in fiber pore volume-fiber hornificationas reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 12 publications
4
48
0
3
Order By: Relevance
“…Recent studies [6][7][8] have demonstrated that this practice can also be used prior to transporting feedstock to biochemical conversion facilities without negatively impacting bioconversion efficiencies. These studies confirm a general understanding from wood fiber science that densification of untreated lignocelluloses does not influence the recalcitrance of biomass or produce fiber hornification, i.e., the irreversible collapse of fiber pores due to hydrogen bonding observed in chemically produced fibers upon pressing or drying [9][10][11].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recent studies [6][7][8] have demonstrated that this practice can also be used prior to transporting feedstock to biochemical conversion facilities without negatively impacting bioconversion efficiencies. These studies confirm a general understanding from wood fiber science that densification of untreated lignocelluloses does not influence the recalcitrance of biomass or produce fiber hornification, i.e., the irreversible collapse of fiber pores due to hydrogen bonding observed in chemically produced fibers upon pressing or drying [9][10][11].…”
Section: Introductionsupporting
confidence: 78%
“…One recent study suggested that pelletizing ammonia fiber expansion (AFEX)-treated corn stover at 70°C did not substantially reduce enzymatic saccharification efficiency [13]. This result seems to contradict the current understanding of the deleterious effects of drying and pressing on subsequent enzymatic saccharification [9,10]. Pelletizing utilizes both heat and pressure to increase the energy density of the lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Wet pressing causes similar reduction in fiber swelling as drying (Carlsson and Lindström 1984;Luo et al 2011). However, wet pressing is much less homogenous compared to drying, as the stresses are concentrated at certain parts of the fiber matrix (Carlsson and Lindström 1984).…”
Section: Wet Pressingmentioning
confidence: 99%
“…"Microfibrillar aggregation: Review," BioResources 7(4), 6077-6108 The accessibility of the hydroxyl groups is important for new innovative products from wood that require chemical or enzymatic treatments. For instance, cellulose microfibril coalescence is seen to hinder both the functionality of enzyme complexes (Samejima et al 1998) as well as the actual enzymatic processes (Luo et al 2011). In addition, the reactivity of dissolving pulp in acetylation is said to be dependent on the lateral fibril aggregate dimension (Chunilall et al 2010).…”
Section: Consequences Of Cellulose Microfibril Coalescencementioning
confidence: 99%
See 1 more Smart Citation